Hereditary spastic paraplegia initially diagnosed as cerebral palsy. (2021) - Suchowersky, Oksana; Ashtiani, Setareh; Au, Ping-Yee Billie; McLeod, Scott; Estiar, Mehrdad A.; Gan-Or, Ziv; Rouleau, Guy A.
Abstract: Introduction: Spastic diplegia presenting in infancy is common to both cerebral palsy (CP) and hereditary spastic paraplegia (HSP). We report the clinical and genetic features of a cohort of Alberta patients with a diagnosis of HSP, who were initially diagnosed with CP. Methods: Fourteen patients with an initial diagnosis of CP were identified from an Alberta registry of HSP patients via chart review. Whole exome sequencing (WES) was performed to identify genetic causes. Results: From 90 families in the database, individuals in 29 families had a pediatric presentation of spasticity, with 20 presenting under 3 years of age. Individuals from 14 families had received an initial diagnosis of CP and correct diagnosis was made after neurogenetic assessment due to symptom progression. All had early onset (<3 years) of symptoms. WES identified pathogenic or likely pathogenic mutations in nine cases involving six genes: ATL1, PLP1, PNPLA6, SACS, SPAST, and SYNE1 . In five families, WES did not reveal a genetic etiology but progression of symptoms and positive family history suggests HSP is the most likely diagnosis. Conclusion: In our cohort, 70% of HSP children presenting with spasticity under 3 years had been misdiagnosed with CP. In a young child presenting with spastic diplegia without clear history of prematurity, intrauterine growth restriction, infection or vascular insult, it is important to consider HSP. Accurate diagnosis has implications for prognosis, management, and recurrence risk.